PENGARUH PENAMBAHAN BUBUK DAUN ALPUKAT (Persea americana Mill) TERHADAP KARAKTERISTIK PUDING - Wahyuningtias, Dini; Antarini, Anak agung Nanak; Agustini, Ni Putu (Jurnal Gizi dan Pangan Soedirman, 2024)
Pudding is a dessert made from food ingredients consisting of jelly, milk, sugar and water which are prepared by boiling. Adding avocado leaf powder to making pudding to increase functional food diversity. This research aims to determine the effect of adding avocado leaf powder on the organoleptic characteristics of pudding and to increase the levels of flavonoids and crude fiber. Experimental type with Randomized Block Design (RAK), 5 treatments and 3 repetitions. Treatments P1, P2, P3, P4, P5 were given the addition of 1% , 1.5% , 2% , 2,5% , 3% avocado leaf powder. The results of organoleptic testing showed that the addition of different avocado leaf powder had a significant effect on color 2.96 – 3.97 (neutral – liked), aroma 3.14 – 4.11 (neutral – liked), taste 2.42 – 3, 98 (neutral - like), texture 3.39 – 4.04 (neutral – like), overall acceptability 2.83 – 3.94 (neutral – like), color quality 1.58 – 2.04 (pale green – green old) and texture quality 2.18 – 2.60 (rather dense – dense). The more addition of avocado leaves powder, the higher flavonoid and fiber level will increase. The addition of avocado leaf powder to treatment P2 (1.5%) was the best treatment seen from the average organoleptic value, namely organoleptic color with an average value of 3.76 (like), aroma 3.68 (like) and taste 3.57 (neutral), texture 3.90 (like), overall acceptance 3.52 (neutral), color quality 2.20 (light green), texture quality with an average value of 2.22 (slightly dense) and taste quality 2.31 (slightly sweet)., with a flavonoid content of 48.08 mg/ 100g and a crude fiber content of 3.37% bb.